2019
DOI: 10.1007/s00394-019-02017-1
|View full text |Cite
|
Sign up to set email alerts
|

Moderate chronic ethanol consumption exerts beneficial effects on nonalcoholic fatty liver in mice fed a high-fat diet: possible role of higher formation of triglycerides enriched in monounsaturated fatty acids

Abstract: Moderate chronic ethanol consumption exerts beneficial effects on nonalcoholic fatty liver in mice fed a high-fat diet. Possible role of higher formation of triglycerides enriched in monounsaturated fatty acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
(110 reference statements)
1
3
0
1
Order By: Relevance
“…This finding was consistent with prior MR studies on the association of alcohol with cardiovascular diseases and NAFLD [39][40][41]. However, in our previous study, we found that low-to-moderate drinking regardless of alcohol type was inversely associated with liver fat content [12], which was also observed in mouse models [42,43]. In the current study, the J-shaped correlation between alcohol use and HCC in participants carrying the CC genotype of PNPLA3 rs738409 was consistent among alcohol types.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with prior MR studies on the association of alcohol with cardiovascular diseases and NAFLD [39][40][41]. However, in our previous study, we found that low-to-moderate drinking regardless of alcohol type was inversely associated with liver fat content [12], which was also observed in mouse models [42,43]. In the current study, the J-shaped correlation between alcohol use and HCC in participants carrying the CC genotype of PNPLA3 rs738409 was consistent among alcohol types.…”
Section: Discussionsupporting
confidence: 92%
“…Next, we determined whether oxidative stress was implicated in the immune response gene expression profile as suggested by the increase in macrophage markers by FFC and FFC-EtOH ( Fig 2B ). In a genetic model of obesity, EtOH upregulated oxidative stress markers, such as heme oxygenase 1 ( Hmox1 ) [ 33 ], while EtOH has also been found to downregulate oxidative stress in HFD-fed mice [ 34 ]. In the present model, compared with Chow, FFC-EtOH and FFC significantly upregulated hepatic gene expression of Hmox1 (P = 0.004 and P = 0.0002, respectively), but there was no significant difference in Cyp2e1 gene expression between the diet groups.…”
Section: Resultsmentioning
confidence: 99%
“…An experimental study on mice fed with a high-fat diet and ethanol-added water [ 48 ] suggested that alcohol induced the generation of non-toxic lipid species (including triglycerides enriched in mono-unsaturated fatty acids), reduced the expression of pro-inflammatory and pro-fibrotic genes, and restored mitochondrial function. A downregulation of several pro-apoptotic genes with a concomitant increased expression of anti-apoptotic genes was also detected.…”
Section: Nafldmentioning
confidence: 99%